Pengaruh Gaya Kepemimpinan terhadap Kinerja Karyawan dengan Komunikasi sebagai Variabel Antara - Firmansyah, Deni; Winarto, Jacinta (Jurnal Informatika Ekonomi Bisnis, 2024)
Human resources have a strategic role in the organization and need to be managed properly to achieve organizational effectiveness and efficiency. Leadership style has a significant influence on employee performance. Communication is also an important factor affecting employee performance. The aims of this study were to determine the effect of leadership style on employee performance, effect of leadership style on communication, the effect of communication on employee performance, and the effect of leadership style on employee performance with communication as an intervening variabel. This study involved employees of the Faculty of Medicine, Maranataha Christian University who were used as research samples. Structural Equation Model - Partial Least Square (SEM-PLS) is a data processing method used because the research conducted involves a small sample size with a minimum sample size in the range of 30 - 100 samples. Based on the results of the research conducted, it shows that leadership style has no effect on employee performance, leadership style has a positive and significant effect on communication, communication has a positive and significant effect on employee performance, and leadership style has a positive and significant effect on employee performance with communication as an intermediate var